2019
DOI: 10.15381/rpb.v26i1.15911
|View full text |Cite
|
Sign up to set email alerts
|

Identificación bioinformática de Polimorfismos de Nucleótido Simple (PNSs) en genes candidatos para las características de la fibra en alpacas (Vicugna pacos)

Abstract: El objetivo fue identificar y predecir la ubicación de polimorfismos de nucleótido simple (PNSs) en genes relacionados al crecimiento de la fibra. Se realizó el estudio con un total de 31 genes de queratina (KRT9, KRT12, KRT13, KRT14, KRT16, KRT18, KRT20, KRT25, KRT1, KRT3, KRT5, KRT6a, KRT6b, KRT6c, KRT7, KRT8, KRT71, KRT80, KRT31, KRT32, KIRT40, KRT81, KRT82, KRT10, KRT15, KRT17, KRT19, KRT2, KRT4, KRT79 y KRT83) asociados con las características de lana, fibra y pelo en ovinos, cabras y humanos respectivame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…As the goal of this study was cytogenetic mapping of candidate genes related to fiber growth and color synthesis, we bioinformatically inspected all VicPac2.0.2 scaffolds containing the 11 mapped markers (Table 2) for additional genes of interest. In scaffold 450 (331,325 bp, NW_005883152.1), which was newly assigned to chr16q12-q13 by FISH mapping KRT15 (Figure 1G), there is a tandemly arranged cluster of five more keratin genes around KRT15 , viz., 5′- KRT31 - KRT15 - KRT13 - KRT9 - KRT14 - KRT16 – 3 ′ (Fernández et al, 2019). Thus, our results allow the assignment of five more keratin genes to chr16q12-q13 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…As the goal of this study was cytogenetic mapping of candidate genes related to fiber growth and color synthesis, we bioinformatically inspected all VicPac2.0.2 scaffolds containing the 11 mapped markers (Table 2) for additional genes of interest. In scaffold 450 (331,325 bp, NW_005883152.1), which was newly assigned to chr16q12-q13 by FISH mapping KRT15 (Figure 1G), there is a tandemly arranged cluster of five more keratin genes around KRT15 , viz., 5′- KRT31 - KRT15 - KRT13 - KRT9 - KRT14 - KRT16 – 3 ′ (Fernández et al, 2019). Thus, our results allow the assignment of five more keratin genes to chr16q12-q13 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a set of exonic and intronic SNPs located in candidate genes for fiber quality and color include 302 SNPs (Accession code: ERZ1694264) as follows: KRT s (205), KRTAP s (56), MC1R (1), ASIP (2), KIT (18), TYRP1 (1). Similarly, SNPs reported in the literature for KRT s (16) [ 15 ], MC1R (1) [ 13 ], and TYRP1 (2) [ 14 ], are included.…”
Section: Resultsmentioning
confidence: 99%
“…A list of these SNPs and their corresponding MAFs are presented in Table S8 . With the exception of the 16 SNPs reported in the literature for these candidate genes [ 12 , 14 , 15 ], all other SNPs are novel and have now been positively identified by genotyping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a high-density bovine single nucleotide polymorphism (SNP) microarray to genotype alpacas, More et al [8] uncovered 6756 conserved SNPs between bovines and alpacas. Other studies have reported SNPs and other variants identified at candidate genes for fiber quality and color traits [9][10][11][12][13][14]. A recent study reported the development of an alpaca 76K SNP microarray [15], which is now available.…”
Section: Introductionmentioning
confidence: 99%